2023
DOI: 10.3390/agronomy13020342
|View full text |Cite
|
Sign up to set email alerts
|

Smart Irrigation Systems in Agriculture: A Systematic Review

Abstract: This research aims to carry out a systematic review of the available literature about smart irrigation systems. It will be focused on systems using artificial intelligence techniques in urban and rural agriculture for soil crops to identify those that are currently being used or can be adapted to urban agriculture. To this end, a modified PRISMA 2020 method is applied, and three search equations are formulated. From those filters, and after a screening process, 170 articles are obtained. These articles are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The experiments conducted demonstrated that the proposed method could save both water and energy. The study conducted by (Vallejo-Goḿez et al, 2023) provided a systematic review using a modified version of the PRISMA 2020 approach to identify important aspects related to smart technologies used in irrigation systems. The review emphasized, as shown in Supplementary Figure 2, that there was a recent increase in research on smart technologies for irrigation system control and modelling.…”
Section: Related Workmentioning
confidence: 99%
“…The experiments conducted demonstrated that the proposed method could save both water and energy. The study conducted by (Vallejo-Goḿez et al, 2023) provided a systematic review using a modified version of the PRISMA 2020 approach to identify important aspects related to smart technologies used in irrigation systems. The review emphasized, as shown in Supplementary Figure 2, that there was a recent increase in research on smart technologies for irrigation system control and modelling.…”
Section: Related Workmentioning
confidence: 99%
“…By incorporating real-time climatic and soil moisture data, the HEPSIS can adapt Working scheme of HEPSIS, reproduced here from [9]. irrigation scheduling based on predicted temperature, and precipitation changes, thereby optimizing water utilization and reducing dependency on manual adjustments [26,27]. Some benefits of the smart irrigation system for rice crops over conventional systems are presented in Figure 5.…”
Section: Hybrid Energy Powered Smart Irrigation Systemmentioning
confidence: 99%
“…The methodology adopted in the present study is inspired by the PRISMA 2020 guidelines [30]. A new strategy was designed by intergrading the PRISMA 2020 guidelines and the review approaches used by other researchers [31][32][33]. The literature related to each sub-domain was searched according to four approaches, illustrated in Figure 3.…”
Section: Review Strategy and Exploration Of Literaturementioning
confidence: 99%